Pengaruh Audit fee, Audit Quality, Audit committee terhadap Tax Avoidance pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia tahun 2018-2020 - Lanang Galih Prasetyo; Isna Rahmawati (ITB AAS INDONESIA, 2023)
This research aims to find and examine the effect of Audit fee, Audit Quality, Audit committee on Tax Avoidance in manufacturing companies listed on the indonesia stock exchange in 2018–2020. The sampling technique was carried out by purposive sampling method with 39 companies selected with total research observation is 117. This Research measured Tax Avoidance with Current Effective Tax Rate. This analysis technique used in this study is multiple linear regression analysis with Eviews 9. The results of the study reveal that Audit fee and Audit committee have a negative significant effect on Tax Avoidance, so the hypothesis was accepted. Other result reveal that Audit Quality do not have a significant effect on Tax Avoidance, so the hypothesis was rejected. In additional, the control variable return on asset and firm size has a significant positive effect on Tax Avoidance.